2021
DOI: 10.3892/ijmm.2021.4915
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the roles of melatonin in bone tissue and bone‑related diseases (Review)

Abstract: Bone-related diseases comprise a large group of common diseases, including fractures, osteoporosis and osteoarthritis (OA), which affect a large number of individuals, particularly the elderly. The progressive destruction and loss of alveolar bone caused by periodontitis is a specific type of bone loss, which has a high incidence and markedly reduces the quality of life of patients. With the existing methods of prevention and treatment, the incidence and mortality of bone-related diseases are still gradually i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 164 publications
(209 reference statements)
1
32
0
Order By: Relevance
“…The cytokines involved in systemic inflammation and acutephase reactions are TNFa and IL-6. Elevated serum cytokine levels, particularly IL-6 and TNFa, were observed in obese subjects (59,60). The obesity patients with increased BMI had abnormal circulation of inflammatory cytokines and are strongly associated in developing severe respiratory failure in COVID-19 (61,62).…”
Section: Details Of Top 10 Melatonin Targets In Treating Obesitymentioning
confidence: 98%
“…The cytokines involved in systemic inflammation and acutephase reactions are TNFa and IL-6. Elevated serum cytokine levels, particularly IL-6 and TNFa, were observed in obese subjects (59,60). The obesity patients with increased BMI had abnormal circulation of inflammatory cytokines and are strongly associated in developing severe respiratory failure in COVID-19 (61,62).…”
Section: Details Of Top 10 Melatonin Targets In Treating Obesitymentioning
confidence: 98%
“…A meta-analysis showed that melatonin supplementation (topical and systemic) in periodontitis patients improved key periodontal parameters including pocket depth and clinical attachment loss 129 . Researches of melatonin on bone repair and regeneration showed that melatonin could promote new bone regeneration and increase the number of osteoblast-like cells 130 . A systematic review and meta-analysis of melatonin adjuvant therapy for periodontitis illustrated that melatonin can significantly improve the periodontal status after non-surgical treatment for periodontitis, and the efficacy is correlated with drug dose 131 .…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…The imbalance of endogenous hormones, including melatonin, leads to the expression of inflammation-related cytokines and matrix degradation-related proteases in articular cartilage, causing cartilage erosion, synovitis, and osteophyte formation ( Hossain et al, 2019 ). Compared with other drugs, melatonin has a wide range of advantages and almost no side effects ( Lu et al, 2021b ).…”
Section: The Role Of Melatonin In the Skeletal Muscle Systemmentioning
confidence: 99%